Pertanggungjawaban Pidana Pers dalam Tindak Pidana Pencemaran Nama Baik Dihubungkan dengan Undang-Undang Nomor 40 Tahun 1999 Tentang Pers (Studi Putusan Nomor 46./Pid.Sus/2021/Pn.Pip) - Nurdin Nurdin; Deny Guntara; Muhamad Abas (UNES Law Review, 2023)
In a democratic country, press freedom is very important. As one of the pillars of democracy, the Press Institution has an important role in translating the value of freedom of opinion, obtaining reliable information, and trying to unite the nation. Press workers believe that the detention of columnists during this fair period has really stifled the imagination of press workers and endangered opportunities for articulation as guaranteed in the constitution and Law Number 40 of 1999 concerning the Press. Law Number 40 of 1999 concerning Press Review Decision Number 46./Pid relates to the issues raised in this article regarding criminal liability of the press for acts of defamation. Based on Law Number 40 of 1999 concerning the Press, the person responsible for news material is the media editor, usually represented by the Editor-in-Chief (Pemred), if legal collection occurs. This article uses a normative method to determine the criminal liability of the press. A press regulatory responsibility framework could also be imposed on press organizations. “Vicarious Liability” is the term for this kind of responsibility.